Reality therapy for the 21st century - Wubbolding, Robert E. (USA : Taylor & Francis Group, 2000)
The books goal is to enhance the skills of helpers so that clients may live more effective lives through a total balance of love, health, and happiness.
Includes bibliographical references and index.
Keywords: Reality therapy; Psychotherapy